{Functional wiring of proteostatic and mitostatic modules ensures transient organismal survival during imbalanced mitochondrial dynamics} - Gumeni, Sentiljana; Evangelakou, Zoi; Tsakiri, Eleni N.; Scorrano, Luca; Trougakos, Ioannis P. (Redox Biology, 2019)
Being an assembly of protein machines, cells depend on adequate supply of energetic molecules for retaining their homeodynamics. Consequently, mitochondria functionality is ensured by quality control systems and mitochondrial dynamics (fusion/fission). Similarly, proteome stability is maintained by the machineries of the proteostasis network. We report here that reduced mitochondrial fusion rates in Drosophila caused developmental lethality or if induced in the adult accelerated aging. Imbalanced mitochondrial dynamics were tolerable for various periods in young flies, where they caused oxidative stress and proteome instability that mobilized Nrf2 and foxo to upregulate cytoprotective antioxidant/proteostatic modules. Consistently, proteasome inhibition or Nrf2, foxo knock down in young flies exaggerated perturbed mitochondrial dynamics toxicity. Neither Nrf2 overexpression (with concomitant proteasome activation)nor Atg8a upregulation suppressed the deregulated mitochondrial dynamics toxicity, which was mildly mitigated by antioxidants. Thus, despite extensive functional wiring of mitostatic and antioxidant/proteostatic modules, sustained loss-of mitostasis exhausts adaptation responses triggering premature aging.
Keywords: Aging; Drp1; Mitofusins; mitostasis; Opa1; Proteostasis